Sei sulla pagina 1di 9

4x 2 4x + 4y 2 12y 26 = 0

y = x 2

9

y = bx

2

(x a) 2 + (y b) 2 = r 2

x 2 2ax + a 2 + y 2 2by + b 2 r 2

x 2 + y 2 2ax 2by + a 2 + b 2 r 2

2a = m 2b = n a 2 + b 2 r 2 = p

x 2 + y 2 + mx + ny + p =

0

= 0

= 0

4x 2 + 4y 2 4x 12y 26 = 0 ⇐⇒ x 2 + y 2 x 3y 13

2

= 0

a

b

r

= m

2

= n

2

= = 1

1

2

3

2

2

= = 3

2

= a 2 + b 2 p = ( 1 2 ) 2 + ( 3 ) 2 (13 ) = 9 = 3

2

2

x 2 2 + y 3 2 = 3 2 y = 3 + 3 2 x

1

2

2

1

2 2

S

4

= 3+

1

2

1

2

3 2 x

1

2 2

dx =

x 1 2 = 3 sin t,

dx = 3 cos tdt,

x

x = 3 + 2 t = arcsin 1 = π

1

2 t = 0

1

=

2

=

π

0

2

3 2 3 2 sin 2 t·3 cos t dt = π 3 2 cos 2 t dt = 3 2 π

0

2

0

2

S

4

= 3 2 π u 2

4

S = 3 2 π u 2

1 + cos 2t

2

dt = 3 2 2 + 1

t

4 sin 2 2t

π

2

0

x = 0 x = b

b

0

bx x 2 dx = bx 2 x 3

2

3

b

0

= b 3

2

b 3

3

9

2

b

3

2

b 3

3

= 9

2

b = 3

z 3 + z 2 (5i 6) + z(9 24i) + 18 + 13i = (z + i)(az 2 + bz + c)

z 3 + z 2 (5i 6) + z(9 24i) + 18 + 13i = 0

z + i

 

5i 6

9 24i

13i + 18

i

i

4 + 6i

13i 18

 

4i 6

13 18i

 

az 2 +bz+c = z 2 +(4i6)z+(1318i)

a = 1, b = 4i 6, c = 13 18i

(z + i)(z 2 + (4i 6)z + (13 18i)) = 0,

z = 6 4i ± (6 + 4i) 2 4(13 18i)

= 6 4i ± 32 + 24i

2

= 32i± 8 + 6i

2

8 + 6i

8 + 6i = p + qi p, q R

(p + qi) 2 = 8 + 6i p 2 q 2 + 2pqi = 8 + 6i p pq 2 = q 3 2 = 8

|p + qi| 2 = |− 8+6i| p 2 +q 2 = |− 8+6i| = 10 2p 2 = 2 p = ±1 p = 1 q = 3 p = 1 q = 3

z = 3 + 2i ± 8 + 6i = 3 + 2i ± (1 + 3i) = 4 2 + i 5i

z 1 = i

  z 3 = 2 5i

z 2 = 4 + i

w = q 2

d ( A, B ) = √ 16 + 4 = 2 √ 5 d

d(A, B)

= 16 + 4 = 2 5

d(A, C)

= 4 + 16 = 2 5

d(B, C)

= 4 + 36 = 2 10

d 2 (A, B) + d 2 (A, C) = d 2 (B, C)

a

+ bx

c

+ dx

cx + d

ax cx + + b

= 0

d = q Q

cqx + dq = ax + b (cq a)x = b dq

a

b = dq

= cq a = cq

a

c

b

d

= 0

r Q a = cr b = dr

ax

+ b

d = crx + dr

cx + d

cx

+

= r Q

2 B A B A B A

· B A

3

= 3

B A

· B A · B A

4

7 6

+ 4

7 6 ·

2

5 =

1

6 8

35 + 35 + 35 =

3 7
3
7

2 1

7 6 ·

5

3

+ 4 6

· 3 + 3

5

7

B A B B · B A B B · B A B B

=

· B A B B

1

7

·

1

5

· 1 + 2

7

· 3 5

· 0 + 4

7 · 2

5 ·

1

2 =

1 7
1
7

x + y = 0

π 2x y + 2z = 1

1

3

x z = 0

1

3

P (λ, λ, λ), λ R

π 1

3

d(P, π) = |2λ (λ) + 2λ 1|

2 2 + (1) 2 + 2 2

= 1

3

λ = 0 A(0, 0, 0)

λ = 2

5 B 2

5 , 2 , 2

5

5

5 → B 2 5 , − 2 , 2 5 5
5 → B 2 5 , − 2 , 2 5 5

π 2x y + 2z = 1

n

r A = (0, 0, 0)

r B = 2

2 5 , 2 5 , 5

+

+

t(2, 1, 2) t(2, 1, 2)

t R

= (2, 1, 2)

r A π 2(2t) (t) + 2(2t) = 1 t = 1 9 9 , 1

2

9 , 9

2

r B π 2( 2 5 + 2t) (5

2 t) + 2( 2

5 + 2t) = 1 t = 1 9

45 , 13

8

45 , 45

8

9 , 1

2

9 ,

9

2

45 , 13

8

45 , 45

8

2 9 , 9 2 45 , − 13 8 45 , 45 8

xy = k (k

= 0)

C(c, k )

A(a, k ) ; B(b, k ) y

a

b

c

v = (c b, k

c

k )

k , c b)

b

n

= ( k

b

c

n

r

= y − k ≡ x − a a k − k c − b
= y − k
x − a
a
k
− k
c − b
b
c
≡ (c − b)x + ( k
− k )y + (b − c)a + k 2 ( c − b ) = 0
c
b
abc

r

(c b)x + ( k

c

k )y + (b c)a + k 2 ( c b ) = 0

b

abc

s

(b a)x + ( k k )y + (a b)c + k 2 ( b a ) = 0

b

a

abc

c

= b b

= a

r abcx kay = k 2 + a 2 bc

s abcx kcy = k 2 + abc 2

r s

x = k 2

abc

y

= abc

k

xy = k